Challenges of nurses' empowerment in the management of patient aggression: A qualitative study - Tahereh Ramezani; Sakineh Gholamzadeh; Camellia Torabizadeh; Farkhondeh Sharif; Laaya Ahmadzadeh (Wolters Kluwer Medknow Publications, 2017)
Background: Patients' aggression in the mental care setting is a global health problem with major psychological, physical, and economic consequences; nurse empowerment to manage this aggressive behavior is an important step in psychiatric nursing. The aim of this study was to explore psychiatric nurses' experiences of the challenges of empowerment in the management of patients' aggression. Materials and Methods: This qualitative study was performed among 20 nurses working in a major referral psychiatric center in Iran during 2014-2016. The purposive sampling method was used for selecting the participants. Data were collected through semi-structured interviews, observations, and filed notes. Inductive content analysis was used for data analysis. Results: Three categories and ten subcategories were identified: inefficient organizational policy (limited human resources, mandatory shifts, shortage of protective equipment, lack of motivational sparks); insufficient job growth (failure to implement training programs, insufficient effort for job competence, lack of clinical guidelines); and deficiencies in the organizational culture (inadequate autonomy and authority, lack of the culture of prevention, culture of fault and blame after an incident). Conclusions: Psychiatric nurses were not satisfied with organizational empowering conditions for the management of patients' aggression and reported low levels of access to learning opportunity, receiving support and essential resources that led to unnecessary use of containment measures. Managers must make every effort to create organizational context that make it possible to empower nurses for optimal practice.